SPERM FACTORS AND EGG ACTIVATION: Phospholipase C zeta (PLCZ1) and the clinical diagnosis of oocyte activation deficiency. Issue 1 (23rd May 2022) - Jones, C; Meng, X; Coward, K
Abstract : Oocyte activation deficiency (OAD) remains the predominant cause of total/low fertilization rate in assisted reproductive technology. Phospholipase C zeta (PLCZ1) is the dominant sperm-specific factor responsible for triggering oocyte activation in mammals. OAD has been linked to numerous PLCZ1 abnormalities in patients experiencing failed in vitro fertilization or intracytoplasmic sperm injection cycles. While significant efforts have enhanced our understanding of the clinical relevance of PLCZ1, and the potential effects of genetic variants upon functionality, our ability to apply PLCZ1 in a diagnostic or therapeutic role remains limited. Artificial oocyte activation is the only option for patients experiencing OAD but lacks a reliable diagnostic approach. Immunofluorescence analysis has revealed that the levels and localization patterns of PLCZ1 within sperm can help us to indirectly diagnose a patient's ability to induce oocyte activation. Screening of the gene encoding PLCZ1 protein is also critical if we are to fully determine the extent to which genetic factors might play a role in the aberrant expression and/or localization patterns observed in infertile patients. Collectively, these findings highlight the clinical potential of PLCZ1, both as a prognostic indicator of OAD and eventually as a therapeutic agent. In this review, we focus on our understanding of the association between OAD and PLCZ1 by discussing the localization and expression of this key protein in human sperm, the potential genetic causes of OAD, and the diagnostic tools that are currently available to us to identify PLCZ1 deficiency and select patients that would benefit from targeted therapy.